2-CONSERVATIVE TREATMENT OF RECTAL ADENOCARCINOMA AFTER NEOADJUVANT CHEMORADIOTHERAPY, IS IT ACCEPTABLE? - Majeed H Alwan (Basrah Journal of Surgery, 2009)
Majeed H Alwan FRCS, FRACS, FACS, Gastrointestinal and General Surgeon, New Zealand 5 Tamworth Place, Gate Pa, TAURANGA, NEW ZEALAND. malwan@paradise.net.nz Abstract The traditional treatment of patients with adenocarcinoma of the rectum involved some form of radical surgery in fit patients followed by radiotherapy, or chemotherapy, or both depending on the stage of the disease and the general condition of the patient. More recently the emergence of neoadjuvant chemoradiotherapy (CRT) has fundamentally changed the management of these patients. Although initially it was recommended for locally advanced disease in an attempt of downstaging the tumour to make it resectable, the indication in using this modality had been widened. In clinical trials, up to 30% complete pathological response (pCR) of tumours have raised the question as to whether surgery, especially radical could be avoided in certain group of patients. A trial of omission of surgery in this group of patients has shown favourable long-term results. This article is an outline of the emerging factors for achieving complete pathological response; the non-operative or the minimal surgery strategies, methods of predicting response to chemoradiotherapy, and means of judging the complete pathological response.